Study of the mechanical, chemical, and surface behaviors of non-woven abrasive made from waste chemically modified tow fibers. (23rd September 2022) - Elaissi, Arwa; Ghith, Adel; Alibi, Hamza; Legrand, Xavier
This article aims to develop a non-woven abrasive material based on textile waste with suitable mechanical properties and surface conditions for the washing treatment of jeans. For this proposal, tow fibers mixed with cotton fibers were reinforced into a polyurethane resin and iron shavings using a coating technique. Abrasive morphology has been examined using MEB analysis. Their elemental composition was identified by EDX Test. The chemical characterization (FTIR) of iron grains was also mentioned. The influence of chemical fiber treatments (alkalinization and cationization) on the mechanical performance and surface properties of nonwovens has been analyzed. To examine fiber-matrix bonding and adhesion, a fiber pullout test was performed. The results showed that nonwoven created with cationized tow fibers improve interfacial properties compared to those made with untreated or alkalized fibers. While their mechanical qualities (Tear test, traction, etc.) were slightly reduced. The variation in the percentages of fibers (tow/cotton) has also an impact on the mechanical strength of the reinforcements. Using the Universal Surface Tester (UST), roughness measurements of nonwovens surface showed that the incorporation of Tow fibers led to significant improvement in the roughness. Cationization at 3% gives good interfacial adhesion and acceptable mechanical performance. This sample has been tried and validated by washing-out experts.